Optimal Regulation Strategy of Electric Vehicle Charging and Discharging Based on Dynamic Regional Dispatching Price - Yu, Shaohua; Du, Zhaobin; Chen, Lidan (Frontiers in Energy Research, 2022)
With the continuous and rapid growth of electric vehicle (EV) ownership, a large number of disorderly charging loads accessed to the regional grid may lead to problems such as widening of the peak-to-valley load difference and deterioration of power quality. This paper proposes an optimal EV charging and discharging regulation strategy based on dynamic regional dispatching price to give full play to the regulation potential of EV vehicle-to-grid (V2G) and reasonably regulate EV charging and discharging behavior to ensure safe, high-quality and economic operation of the grid. Firstly, the EV travel chain model is constructed according to the travel behavior pattern of EV users to obtain the spatial and temporal distribution characteristics of EV charging and discharging loads. Secondly, considering the difference in regional grid operation states, a dynamic update strategy of regional dispatching price integrating power grid spatial and temporal information is proposed. Furthermore, considering the characteristics of EV mobile energy storage and user demand, an EV V2G optimal regulation model that takes into account the interests of distribution system operators, EV aggregators and EV users is established to effectively guide the regulation of EV charging and discharging behavior. Finally, the simulation results show that the proposed strategy can effectively reduce the load deviation of each regional grid, the operation cost of EV aggregators and the charging cost of EV users, and significantly improve the safety and economy of the power system.